Uwierzytelnianie odpisów dokumentów w postępowaniu administracyjnym - Artymionek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents changes to the administrative procedure introduced by the Act of 23 October 2009, amending the laws on authentication of documents. The author analyzes the standard practice nof authentication of documents by officers of public authorities as reflected in the law applicable before and after the entry into force of the Amending Act. Transitional issues are discussed with reference to the validity of the new solutions as applied in relation to pending proceedings. He also indicates diverse errors committed by public authorities in the application of the law, and ultimately answers the question which entities, in the current state of the law, are legally authorized to authenticate documents and credentials in administrative proceedings.
Keywords: dokument urzędowy; uwierzytelnienie dokumentu; uwierzytelnienie poświadczeń; uwierzytelniona kopia dokumentu; streszczenie dokumentu